2018
DOI: 10.3390/en11010184
|View full text |Cite
|
Sign up to set email alerts
|

Time-Section Fusion Pattern Classification Based Day-Ahead Solar Irradiance Ensemble Forecasting Model Using Mutual Iterative Optimization

Abstract: Accurate solar PV power forecasting can provide expected future PV output power so as to help the system operator to dispatch traditional power plants to maintain the balance between supply and demand sides. However, under non-stationary weather conditions, such as cloudy or partly cloudy days, the variability of solar irradiance makes the accurate PV power forecasting a very hard task. Ensemble forecasting based on multiple models established by different theory has been proved as an effective means on improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…The authors suggested GAN-CNN2D for PVPF modeling, although CNN2D achieved the highest scores due to its ability to eliminate non-linear input-output correlations. Correspondingly, the previous literature emphasized the importance of using weather categorization to ensure the effectiveness and accuracy of solar irradiance forecasting models, as weather conditions should always be prioritized for forecasting [52,72,73].…”
Section: Weather Classificationmentioning
confidence: 99%
“…The authors suggested GAN-CNN2D for PVPF modeling, although CNN2D achieved the highest scores due to its ability to eliminate non-linear input-output correlations. Correspondingly, the previous literature emphasized the importance of using weather categorization to ensure the effectiveness and accuracy of solar irradiance forecasting models, as weather conditions should always be prioritized for forecasting [52,72,73].…”
Section: Weather Classificationmentioning
confidence: 99%
“…Zhen et al used multi-level wavelet decomposition to pre-process solar irradiance data to further enhance the prediction accuracy [23]. A new day-to-day model for predicting solar irradiance was created in another Zhen article based on a time-section fusion pattern and mutual iterative optimization [24].…”
Section: Related Workmentioning
confidence: 99%
“…Differently, a multi-level wavelet decomposition is applied by Zhen et al [41] to preprocess the solar irradiance data in order to further improve the day-ahead solar irradiance forecasting accuracy. In Zhen's another paper, a new day-ahead solar irradiance ensemble forecasting model was developed based on time-section fusion pattern classification and mutual iterative optimization [42]. With the emergence of deep learning (DL) models, Qing et al [43] turned to Long Short Term Memory (LSTM) to catch the dependence between consecutive hours of daily solar irradiance data.…”
Section: Literature Reviewmentioning
confidence: 99%